Nuevos registros de aves en el Parque Nacional Iztaccíhuatl-Popocatépetl, Puebla, México/New records of birds at National Park Iztaccíhuatl-Popocatépetl, Puebla, Mexico - Estay Stange, Andrés E.; Rodríguez-Estrella, Ricardo; Bautista Ortega, Amando (Instituto de Ecología, A.C., 2015)
We reported four new bird species for the National Park Iztaccíhuatl-Popocatépetl (Megascops trichopsis, Aegolius acadicus, Athene cunicularia and Antrostomus arizonae), and five new records for the state of Puebla, four owl species (Megascops kennicotti, M. trichopsis, Aegolius acadicus and Athene cunicularia), one goatsucker (Antrostomus arizonae).